2021
DOI: 10.4067/s0718-33992021000100146
|View full text |Cite
|
Sign up to set email alerts
|

Distributive justice and police legitimacy: the demographic and geographical distribution of police ID checks in Spain

Abstract: The distribution of police activity throughout society is a key issue for distributive justice and police legitimacy. This article presents two studies on the distribution of police identification checks in Catalonia (Spain) using data provided by Mossos d'Esquadra (the Catalan Regional Police). The first study explores the demographic distribution of ID checks, in other words, which groups of people are more likely to be stopped and have their identification checked by police. The second study examines the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Criminological studies have primarily focused on identifying the factors that influence perceptions of police power. For example, research has found that perceptions of police legitimacy are associated with the equitable distribution of police resources (López, 2021;Tyler & Huo, 2002), law-abiding police behaviour (Sun et al, 2018) effectiveness in crime control (Bradford et al, 2012), and procedural fairness (Mazerolle et al, 2013b;Walters et al, 2019). However, the relative importance of each factor may vary depending on the cultural context in which police-citizen relations take place (Jackson et al, 2014;Tankebe, 2009).…”
Section: Police Legitimacy and Procedural Justicementioning
confidence: 99%
“…Criminological studies have primarily focused on identifying the factors that influence perceptions of police power. For example, research has found that perceptions of police legitimacy are associated with the equitable distribution of police resources (López, 2021;Tyler & Huo, 2002), law-abiding police behaviour (Sun et al, 2018) effectiveness in crime control (Bradford et al, 2012), and procedural fairness (Mazerolle et al, 2013b;Walters et al, 2019). However, the relative importance of each factor may vary depending on the cultural context in which police-citizen relations take place (Jackson et al, 2014;Tankebe, 2009).…”
Section: Police Legitimacy and Procedural Justicementioning
confidence: 99%
“…10 More recently, the social alarm has moved towards the unaccompanied migrant children and adolescents, most of them coming from Marrakesh (42%), Mali (17.4%), Algeria (16.6%) and Senegal (13.3%) (Fiscsalía General del Estado, 2021), that are seen as a threat in some political and media discourses, generating social alarm, suspicion and rejection 11 (García España & Carvalho da Silva, 2019;García España et al, 2021). In general, the African descendent population is linked to crime by media in Spain (Cea d'Ancona & Valles Martínez, 2021) and they are frequently stopped by the police (APDHA & IPAZ-UGR, 2016; García Añon et al, 2013;López Riba, 2021). The last group highlighted by the literature as being criminalised by the media and the population are Eastern Europeans.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Stereotypes link these people to gangs responsible for violent burglaries and robberies. Even the police share this belief (Schmitt & Pernas, 2008) and subsequently they are more targeted in police activity (APDHA & IPAZ-UGR, 2016; García Añon et al, 2013;López Riba, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations